Challenges in Positioning and Penetration of a New Medicine in the Minds of The Physicians: An Opinion Survey of Medical Representatives - DOBHAL, NIDHI (International Journal of Psychosocial Rehabilitation, 2021)
This study examines the challenges faced by medical representatives in positioning and penetrating a new medicine in the minds of physicians. A survey of medical representatives was conducted to explore the key challenges, which include competition from established brands, limited time with physicians, lack of physician awareness, and limited access to physicians. These challenges can hinder the successful introduction of new medicines in the market. Therefore, it is essential for pharmaceutical companies to develop effective marketing strategies to overcome these obstacles. The findings of this study can inform the development of such strategies, which can lead to successful positioning and p